Effect of zeaxanthin addition to feeding on non-specific immune performance in the Penaeus vannamei - Mi, Hanwen (Technium BioChemMed, 2022)
In recent years, the market demand for aquatic products has also been increasing. However, due to environmental pollution, many aquatic organisms become weaker in immunity and thus develop various diseases, which affect overall aquatic production. Currently, people enhance the immune performance of aquatic animals by adding peptidoglycan, astragalus polysaccharide, and vitamins to aquatic feeds; the addition of zeaxanthin (Zeaxanthin, 3,3'-dihydroxy-b-carotene) has not been reported to enhance immunity. This experiment investigated the effect of zeaxanthin on some immune indicators in South American white shrimp. The results of the kit showed that zeaxanthin had a significant effect on the activity of lysozyme, NOS and CAT (P<0.05), with a decreasing trend in the activity of lysozyme and an increase in the activity of nitric oxide synthase and catalase as the concentration of zeaxanthin added increased. Next, there were no significant differences in the activities of malondialdehyde (MDA), superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX). Among them, the addition of 0.5% zeaxanthin had the greatest effect on NOS and CAT activity. As shown above and combined with the actual economic benefits, 0.5% zeaxanthin was selected as the best feed additive.